Developing the Use of Quality Indicators in Sterilization Practices - H Jabbari; H Alikhah; N Sahebkaram Alamdari; M Naghavi Behzad; E Mehrabi; L Borzui; F Bakhshian (Tehran University of Medical Sciences, 2012)
Background: Health-care-associated infections are a major threat to the safety of patient care. Control of such problem is a major criterion for hospital accreditation. This study was aimed to determine the developing use of chemical (class 6 products) and biological indicators in Tabriz district hospitals since 1997 to 2011. Methods: We conducted this time-trend interventional study with all of the public and private hospitals, which counted to 21 in Tabriz district as a sample. The situations of indicator use were presented for each time in the base of indicator groups. Furthermore, the results were showed in the base of hospital groups. Results: All of district hospital (n=21) with 74 autoclave machine and 22 central sterilization room were studied. The result of second time study in 2008 showed a markedly improvement in the control of sterilization processes. Furthermore, we continued our intervention results 6 month later in 2009 and 2 years later in 2011. The most striking result were use of chemical indicator in 100% of hospitals. However, there are defects in the use of biological indicators (63.65%). Conclusion: The most obvious finding was significant improvement in sterilization control especially in development the use of chemical indicators. The finding of this study has a number of important implications for hospital managers and infection control practitioners such as continuous practical training of CSSD personnel in hospitals and mandating of indicator using in all sterilization process with controlling of this subject in evaluation and accreditation of hospital programs.